Screening for antimicrobial activity of extracts from Zingiber officinale Rosc. var. rubrum Theilade - yani, Linda; M.H, Norazian; Zakaria, Muhamad; Abdul Rahman, Noorsaadah; K, Norzulaani (Malaysian Journal of Science, 2001)
Extracts from the rhizomes of Zingiber officinale Rosc. var. rubrum Theilade were tested for antimicrobial activity against 11 bacterial and 6 fungal species. Compared with standard antibiotics, extracts had low to moderate activity except for the petroleum ether extract. The activity spectrum is wide against gram-positive and gram-negative bacterial as well as fungal tested. The extracts that showed the highest antimicrobial activity have similar antifungal activity with 5- Fluorocytosine at 10Âµg/disc against Trichophyton mentagrophytes. Other extracts showed low to moderate antibacterial activity when compared with gentamicin at 10Âµg/disc against Bacillus subtilis, Staphylococcus aureus (ATCC 24213 and ATCC 29213), Streptococcus faecalis, Micrococcus luteus and Proteus vulgaris.